Dietary inclusion of mussel meal enhances performance and improves feed and protein utilization in common sole (Solea solea, Linnaeus, 1758) juveniles. (28th September 2015) - Mongile, F.; Mandrioli, L.; Mazzoni, M.; Pirini, M.; Zaccaroni, A.; Sirri, R.; Parma, L.; Gatta, P. P.; Sarli, G.; Bonaldo, A.
Summary: The present study was carried out to test different mussel meal (MM) dietary levels in combination with fishmeal (FM) on the growth performance, fatty acid composition and liver histology of common sole, Solea solea juveniles to highlight the growth potential of this species. Four isoproteic (53%) and isolipidic (11%) pelletized diets were formulated to contain graded levels of mussel meal, MM0 (0%), MM25 (25%), MM50 (50%) and MM75 (75%), up to 75%. Sole juveniles (initial individual mean body weight 13.1 ± 2.3 g, n = 840) were fed to satiation for 91 days. Seventy fish per tank (500‐L, 0.64 m 2 bottom surface) were reared in 12 tanks (3 tanks per treatment) at 20 ± 1°C. Diets containing MM (MM25, MM50 and MM75) gave a significantly higher specific growth rate (SGR, 1.27 ± 0.01, 1.38 ± 0.06 and 1.40 ± 0.05, respectively), higher feed intake and lower feed conversion rate (FCR, 1.09 ± 0.01, 1.00 ± 0.04 and 0.98 ± 0.02, respectively) when compared to the FM‐based diet (MM0, SGR, 0.98 ± 0.11, FCR, 1.52 ± 0.13). Carcass proximate composition was not influenced by dietary treatments, with the exception of the significantly lower lipid content in the MM75 group. Protein efficiency ratio (PER) and gross protein efficiency (GPE) were significantly improved by the mussel meal inclusion (PER, 1.29 ± 0.12, 1.76 ± 0.01, 1.89 ± 0.06, 1.95 ± 0.08; GPE, 25.29 ± 1.85, 33.38 ± 0.89, 35.96 ± 1.36, 36.59 ± 1.05 in MM0, MM25, MM50 and MM75, respectively). A significant decrease in the viscerosomatic index was observed in fish fed with MM50 and MM75 in comparison to MM0. The hepatosomatic index of fish fed with MM0 and MM25 was higher than that of fish fed with MM75, although the histological examination of liver parenchyma in all experimental groups showed a uniformly abundant accumulation of lipid droplets. Carcass fatty acid composition was significantly affected by dietary treatments, reflecting the dietary fatty acid profile. According to these results, the inclusion of MM in experimental FM‐based diets improved the performance and feed utilization of common sole juveniles. The inclusion of MM in the present trial allowed a higher SGR than that registered in previous growth trials on common sole. This study could provide useful information to detect effective ingredients for practical diets in Solea solea . It also seems advisable to consider an inclusion of at least 25% MM in the experimental reference diet to be used for further application towards the development of specific diets for this species.